2020
DOI: 10.1021/jasms.0c00202
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Endogenous Molecules in Coffee Beans by Atmospheric Pressure Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry Imaging

Abstract: Mass spectrometry imaging (MSI) is a promising chemical imaging method. Among various endogenous molecules, mapping the concentration and the spatial distribution of specific compounds in the coffee bean tissue is of tremendous significance in its function research, as these compounds are critical to grading coffee beans at the molecular level, determining the geographical origin, and optimizing storage conditions of coffee beans. In this paper, we established an atmospheric pressure (AP) matrixassisted laser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Overview of Lentil MALDI-MSI Analysis. Similar to the MALDI-MSI mechanism described in related reports, 30 a typical analysis procedure of MALDI-MSI for lentils at different germination time points is provided in Figure 1. First, lentil tissues were collected and cryo-sectioned at 12, 24, 36, 48, 60, and 72 h after germination.…”
Section: Resultsmentioning
confidence: 99%
“…Overview of Lentil MALDI-MSI Analysis. Similar to the MALDI-MSI mechanism described in related reports, 30 a typical analysis procedure of MALDI-MSI for lentils at different germination time points is provided in Figure 1. First, lentil tissues were collected and cryo-sectioned at 12, 24, 36, 48, 60, and 72 h after germination.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it prevents delocalization of biomaterials in the tissue section by a finger heat since the sample is mounted on a stainless steel slide using the tape and vacuum-dried on a frozen aluminum plate . Tape-supported mounting is suitable for small samples and/or less sticky tissues. − This is because the adhesive tape adheres to the surface of the sample block and supports it before it is cut with the blade. In this study, carbon double-sided tape was used to mount the fly head section for conductivity consideration, as shown in Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
“…4h ). 118 Distribution of phytochemicals in the dried root of Isatis tinctoria was carried out by Li Xing Nie et al and 118 compositions were identified without extraction and isolation in 2021. Using partial least squares regression (PLS), samples collected from four habitats were differentiated unambiguously.…”
Section: Applications Using Ap Maldimentioning
confidence: 99%